HEUTAGOGY APPROACH IN MERDEKA CURRICULUM - Rusdiono Muryanto (Universitas Pendidikan Indonesia, 2022)
The Covid-19 crisis in the world has significantly impacted everything, including the world of education. Almost all countries have closed the face-to-face teaching and learning process in schools at all levels of education. Many countries then improve their education system so students can catch up in learning. In Indonesia, the Ministry of Education, Culture, Research, and Technology is also trying to restore education by issuing the ‘Kurikulum Merdeka policy. This study examines the appropriate learning approach in implementing the ‘Kurikulum Merdeka’ in primary and secondary education units. A heutagogical approach is an approach in education where learners are fully centered and determined to learn. Students can be active and proactive and create fun learning for themselves. Based on the studies carried out, with a heutagogical approach and the use of technology, students will be able to master the competencies that have been determined through fun learning, and this can be applied in the Implementation of the ‘Kurikulum Merdeka’ which focuses on the needs of students.